Improved packet classification algorithm based on multidimensional space dynamic division and RFC - CHEN Xiaoyu, LU Yueming (网络与信息安全学报, 2018)
According to the existing problem that memory usage grows exponentially with the size increase of rule set in RFC (recursive flow classification) algorithm, an improved packet classification algorithm, HRFC (Hybrid-RFC) was put forward. The new algorithm completes the dynamic division of a multidimensional space rule set by a decision tree, accomplishes the mapping of each subset with multiple phase reduction trees, so as to realize fast and efficient packet classification. The simulation results show that the new algorithm can reduce the space usage effectively while guaranteeing the performance of classification speed.